Beyond Delivery - Peck, E. author. aut Link
XXII, 237 p. 4 illus.
Keywords: Beyond Delivery sets out a critique of the mechanical ways in which some policy makers seek to exercise governance over the implementation of their policies. It offers a timely critique of the current British government's approach.